Evaluasi Proses Kredensial Terhadap Kualitas Kerja Perawat Di Rumah Sakit Umum X Bandung - Umayah, Azzahra Khoirunnisa; Ariyani, Nurul Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This research aims to evaluate the credential process on the quality of nurses' work at X Bandung General Hospital. The method used is quantitative with observation data collection techniques, and questionnaires. The population and sample used were 55 respondents, namely nursing employees at the X Bandung General Hospital. This study uses data analysis techniques: Validity Test, Reliability Test, and Spearman Rank Correlation Test. The results of the Spearman Rank Correlation Test show that changes in one variable do not have a significant effect on the other variables, however, there is still a positive relationship between the two variables can be seen from the correlation value of 0.168 and the significance of 0.221 meaning that when the value of